A clinically-relevant mouse model that displays hemorrhage exacerbates tourniquet-induced acute kidney injury - Packialakshmi, Balamurugan; Burmeister, David M.; Anderson, Joseph A.; Morgan, Judah; Cannon, Georgetta; Kiang, Juliann G.; Feng, Yuanyi; Lee, Sang; Stewart, Ian J.; Zhou, Xiaoming (Frontiers in Physiology, 2023)
Hemorrhage is a leading cause of death in trauma. Tourniquets are effective at controlling extremity hemorrhage and have saved lives. However, tourniquets can cause ischemia reperfusion injury of limbs, leading to systemic inflammation and other adverse effects, which results in secondary damage to the kidney, lung, and liver. A clinically relevant animal model is critical to understanding the pathophysiology of this process and developing therapeutic interventions. Despite the importance of animal models, tourniquet-induced lower limb ischemia/reperfusion (TILLIR) models to date lack a hemorrhage component. We sought to develop a new TILLIR model that included hemorrhage and analyze the subsequent impact on kidney, lung and liver injuries. Four groups of mice were examined: group 1) control, group 2) hemorrhage, group 3) tourniquet application, and group 4) hemorrhage and tourniquet application. The hemorrhagic injury consisted of the removal of 15% of blood volume through the submandibular vein. The tourniquet injury consisted of orthodontic rubber bands applied to the inguinal area bilaterally for 80 minutes. Mice were then placed in metabolic cages individually for 22 hours to collect urine. Hemorrhage alone did not significantly affect transcutaneous glomerular filtration rate (tGFR), blood urea nitrogen (BUN) or urinary kidney injury molecule-1 (KIM-1) levels. Without hemorrhage, TILLIR decreased tGFR by 46%, increased BUN by 162%, and increased KIM-1 by 27% (p<0.05 for all). With hemorrhage, TILLIR decreased the tGFR by 72%, increased BUN by 395%, and increased urinary KIM-1 by 37% (p<0.05 for all). These differences were statistically significant (p<0.05). While hemorrhage had no significant effect on TILLIRinduced renal tubular degeneration and necrosis, it significantly increased TILLIRinduced lung total injury scores and congestion, and fatty liver. In conclusion, hemorrhage exacerbates TILLIR-induced acute kidney injury and structural damage in the lung and liver.